Dorokdok Industry as a Gastronomy Tourism Attraction in Leles District, Garut Regency, Indonesia - Jannah, Abyta Nurul; Putri, Dias Pratami (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2024)
This study investigates the potential of the Dorokdok industry in Leles District, Garut Regency, as a unique gastronomic tourism attraction. Leles District, one of 42 sub-districts in Garut Regency, serves as a significant production hub for Dorokdok—a traditional local snack—and is a key entry point for tourists. This strategic location offers promising opportunities to develop Dorokdok as a distinctive culinary attraction for visitors. The research aims to identify the gastronomic characteristics of Dorokdok and evaluate the industry’s potential to attract gastronomic tourism. Data were collected through interviews with business owners, government officials, suppliers, and industry experts, along with surveys of 84 respondents. Utilizing Snowball and Purposive sampling methods, the data were analyzed through descriptive qualitative techniques. The findings reveal that Dorokdok has significant potential as a gastronomic tourism attraction in Leles District, with six main production centers distributed throughout the area. This study contributes insights for stakeholders seeking to develop the Dorokdok industry to enhance the local economy and promote regional tourism.